Indigenous curatorial practices and their modes of becoming Práticas curatoriais indígenas e seus modos de vir-a-ser Isabela Hueara Carneiro 2025 - Isabela, Hueara Carneiro (Taideyliopiston Kuvataideakatemia, 2025)
This thesis investigates indigenous curatorial practices and their modes of constitution, based on a dual approach: the analysis of theoretical and methodological foundations and direct dialogue with active indigenous curators. The research starts from a situated perspective—Uchinanchu-Brazilian—and develops as a methodological exercise that articulates personal experience, indigenous references, and contemporary curatorial practices. In the first chapter, I present a contextual cartography that locates my trajectory, marking the displacements and belongings that inform this investigation. The second chapter discusses the emergence of contemporary indigenous art as a category and strategy, examining its insertion in art institutions and its role in confronting hegemonic narratives. The third chapter systematizes principles and debates surrounding indigenous curatorial methodologies, contrasting them with Western curatorial paradigms and problematizing processes of institutionalization. In the fourth chapter, I delve deeper into these issues based on conversations with Edson Kayapó and Arissana Pataxó, who offer situated perspectives on temporality, collectivity, and belonging as curatorial axes. Based on these conversations, I develop three essays that analyze how these concepts are articulated both in indigenous curatorial practice and in my own experience as a researcher. The choice of full transcripts and co-presence writing seeks to move away from extractivist approaches and affirm the relational dimension of knowledge production. In my final thoughts, I summarize the main contributions of the research, emphasizing that indigenous curatorship cannot be reduced to a single methodology, but must be understood as a plural, situated, and constantly evolving field.
Keywords: Brasilia; Indigenous art; Curatorship; Methodology; Brazil; alkuperäiskansat; kuratointi; metodologia; Praxis